1999
DOI: 10.1080/00220389908422579
|View full text |Cite
|
Sign up to set email alerts
|

Total factor productivity growth in East Asia: A critical survey

Abstract: This article surveys the recent empirical literature on total factor productivity (TFP) growth in East Asia, and the debate about the sources of growth in the region. It is concluded that: (i) the main merit of this literature is that it has helped focus the attention of scholars on the growth process of East Asia; (ii) the theoretical problems underlying the notion of TFP are so significant that the whole concept should be seriously questioned; (Hi) the TFP growth estimates for the region vary significantly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(136 citation statements)
references
References 66 publications
2
131
0
3
Order By: Relevance
“…Identifying TFP growth with technical progress ignores the importance of technical efficiency-change, especially in less-developed countries. Introducing new technologies there without first realizing the full potential of existing ones might be wasteful (Felipe, 1999). Several studies have found that TFP growth in China has been achieved more through technical progress than efficiency improvement (Zheng, Liu, and Bigsten 2003;Zheng and Hu, 2006).…”
Section: Technical Progress Vs Efficiency Improvementmentioning
confidence: 99%
“…Identifying TFP growth with technical progress ignores the importance of technical efficiency-change, especially in less-developed countries. Introducing new technologies there without first realizing the full potential of existing ones might be wasteful (Felipe, 1999). Several studies have found that TFP growth in China has been achieved more through technical progress than efficiency improvement (Zheng, Liu, and Bigsten 2003;Zheng and Hu, 2006).…”
Section: Technical Progress Vs Efficiency Improvementmentioning
confidence: 99%
“…Nadiri (1970) concludes several factors that may influence TFPG: first, specifications of the production 4 function; second, the proper measurement of factor inputs; third, the weight assigned to different inputs; fourth, time period chosen in the study. Felipe (1999) suggests that the measurement of TFPG depends critically on assumptions about production function, measurement of output, measurement of capital, quality adjustment of inputs, cyclical smoothing, time period studied, errors of measurement in the variables, and so on. Chen (1997) also believes that the measurement of TFPG is quite sensitive to the measurement of factor inputs, especially to the extent and scope of the adjustments of quality improvements made to factor inputs.…”
Section: Tfpg Measurementmentioning
confidence: 99%
“…However, the concept of TFP is only applicable to disembodied, exogenous and Hicks neutral technical progress in neoclassical economics. Furthermore, if inputs are not measured correctly, the TFP contains not only disembodied technical progress but also some embodied technical progress (Chen, 1997;Zheng, 1998;Felipe, 1999).…”
Section: Tfpg Measurementmentioning
confidence: 99%
“…However, Singh and Trieu (1999) showed that this conclusion might be flawed, since it was based on comparing results from different methodologies. Other growth accounting exercises for individual East Asian countries have also given mixed results (Felipe, 1999).…”
Section: Sources Of Growth In East Asia: Previous Studiesmentioning
confidence: 99%
“…While some assessments of the "sources of growth" literature (e.g., Felipe, 1999) have questioned this entire approach and its theoretical basis, it remains true that empirical studies have been both numerous and influential. For example, the World Bank (1993) and Hughes (1995) examined the contribution of public policy in economic development; Kim and Lau (1994), Young (1992Young ( , 1995 and Krugman (1994) emphasized capital accumulation in the high performing East Asian economies; Sonobe and Otsuka (2001) advanced a hypothesis that capital deepening associated with transformation of industrial structure has been the major factor for sustaining growth for a long period in East Asia; Hayami and Ogasawara (1999) argued that Japan has continued to depend more heavily on physical capital accumulation mainly due to its characteristic of borrowed-technology based economic growth; and Trieu (1997, 1999) focused more on the role of technological change.…”
Section: Introductionmentioning
confidence: 99%